Analysis of SMK3 implementation on building construction project implementation performance: Case study of the construction of the Menara Mandiri building in Denpasar - Sudiarsa, Made; Wibawa, I Gede Sastra; Wiraga, I Wayan; Dwipa, I G A G Surya Negara R S; Arya, I Wayan; Susila, I Nengah Darma (International research journal of engineering, IT and scientific research, 2025)
The construction industry is inherently associated with a high risk of occupational accidents. A major contributing factor to such incidents is the inadequate implementation of Occupational Safety and Health (OSH) practices. To mitigate these risks, the professional application of the Occupational Safety and Health Management System (OSHMS) is crucial and should comply with relevant laws and government regulations. This study aims to assess the level of OSHMS implementation in the construction of the Menara Mandiri Building in Denpasar and to identify key factors influencing its application. A qualitative descriptive method was employed, with data collected through the use of checklists and questionnaires. The data were analyzed using percentage analysis to determine the implementation level, descriptive statistics (mean values), and ranking analysis to identify influential factors. The findings indicate that the OSHMS implementation level was satisfactory, with a compliance rate of 96.39% and a minor non-compliance rate of 3.61%. The most significant factor influencing the implementation of OSHMS was the availability of occupational safety and health training for workers.